2005
DOI: 10.1016/j.ophtha.2004.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of hyperopia in an elderly population of siblings in Salisbury, Maryland

Abstract: Purpose-To determine whether hyperopia aggregates in families in an older mixed-race population.Design-Cross-sectional familial aggregation study using sibships.Methods-We recruited 759 subjects (mean age, 73.4 years) in 241 families through the population-based Salisbury Eye Evaluation study. Subjects underwent noncycloplegic refraction if best-corrected visual acuity (BCVA) was ≤20/40, had lensometry to measure their currently worn spectacles if BCVA was >20/40 with spectacles, or were considered to be plano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
3
11
1
Order By: Relevance
“…In the present study, there was a trend toward adults older than 40 years being less myopic than younger adults and adolescents. In older groups, there was also a trend toward a decrease in myopia, which agrees with results of Wojciechowski et al, 29 who found a higher prevalence of hyperopia in adults until 75 years of age. The hyperopic shift from the 30s, with a maximum mean hyperopic value in the elderly, also agrees with previous 2000 results of Montés-Micó and Ferrer-Blasco 18 for a much larger population in the same region of Spain.…”
Section: Age-related Changes In the Human Visual Systemsupporting
confidence: 91%
“…In the present study, there was a trend toward adults older than 40 years being less myopic than younger adults and adolescents. In older groups, there was also a trend toward a decrease in myopia, which agrees with results of Wojciechowski et al, 29 who found a higher prevalence of hyperopia in adults until 75 years of age. The hyperopic shift from the 30s, with a maximum mean hyperopic value in the elderly, also agrees with previous 2000 results of Montés-Micó and Ferrer-Blasco 18 for a much larger population in the same region of Spain.…”
Section: Age-related Changes In the Human Visual Systemsupporting
confidence: 91%
“…More extreme refractive errors show even greater familial aggregation than do milder forms (107, 109). Moreover, children of myopic parents tend to have longer eyes (110) and are more likely to develop myopia during childhood or adolescence (111–113).…”
Section: Genetic Influences On Refractive Errormentioning
confidence: 99%
“…So far, it is unclear whether myopia develops from adaptive physiologic responses to visual demands of modern societies or instead develops from physiologically inappropriate processes that may override, rather than exploit, normal regulatory mechanisms (Stone, 2008). Genetic factors have been implicated in the etiology of both myopia and hyperopia (Wojciechowski, Cogdon, Bowie, Munoz, Gilbert & West, 2005). Twin and family studies have long suggested a genetic component in myopia and several chromosomal loci have been linked with human myopia, including high myopia (Hornbeak & Young, 2009, Young, Metlapally & Shay, 2007).…”
Section: Why Refractive Errors?mentioning
confidence: 99%